Efek Pasca Penutupan TikTok Shop pada Volume Pendapatan Jasa Pengiriman J&T Express dalam Perspektif Syariah: Studi pada Werehouse J&T Express di Bandar Lampung - Nurhayati Nurhayati; Mayang Putri; Hanif Hanif (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The closure of TikTok Shop has caused significant polemics, especially regarding the responsibility of e-commerce platforms as well as operational impacts on business and society, such as decreased revenue in the shipping sector, including J&T Express Bandar Lampung. This study aims to analyse the post-closure impact of TikTok Shop on J&T Express' revenue volume, and evaluate it from a sharia perspective. Using a qualitative approach, data were collected through questionnaires, observations, interviews, and documentation in the form of reports and literature. Data collection techniques include field observations and interviews with relevant parties. The results showed that the closure of TikTok Shop had a significant impact, reflected in the decrease in receipt volume at J&T Express Tanjung Gading, where around 70% of revenue came from the platform. From a sharia perspective, the closure of TikTok Shop can be considered appropriate if the platform violates sharia principles, such as justice, responsibility, and consumer protection. If the shutdown contributes to the reduction of exploitation and economic injustice, then the action is in line with sharia values.